Fractional kalman filter algorithm for the states, parameters and order of fractional system estimation - Sierociuk, Dominik; Dzieliński, Andrzej (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents a generalization of the Kalman filter for linear and nonlinear fractional order discrete state-space systems.Linear and nonlinear discrete fractional order state-space systems are also introduced. The simplified kalman filter for thelinear case is called the fractional Kalman filter and its nonlinear extension is named the extended fractional Kalman filter.
Keywords: discrete fractional state-space systems; fractional Kalman filter; parameters estimation; order estimation; extended fractional Kalman filter